2015
DOI: 10.1371/journal.pone.0128158
|View full text |Cite
|
Sign up to set email alerts
|

Some See It, Some Don’t: Exploring the Relation between Inattentional Blindness and Personality Factors

Abstract: Human awareness is highly limited, which is vividly demonstrated by the phenomenon that unexpected objects go unnoticed when attention is focused elsewhere (inattentional blindness). Typically, some people fail to notice unexpected objects while others detect them instantaneously. Whether this pattern reflects stable individual differences is unclear to date. In particular, hardly anything is known about the influence of personality on the likelihood of inattentional blindness. To fill this empirical gap, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 66 publications
2
8
1
2
Order By: Relevance
“…Those individuals who rated themselves higher in conscientiousness were significantly less likely to notice the unexpected event, and while the relationship was no longer significant after controlling for individual differences in processing speed, the same trend between conscientiousness and IB persisted. This relationship between conscientiousness and IB is in contrast to our own work that used a similar sustained IB task (Wright, Boot, & Morgan, 2013) and other work that used a static IB task (Kreitz, Schuerch, Gibbons, & Memmert, 2015). Kreitz and colleagues (2015) suggest that demands of the primary task may account for differences in findings across studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Those individuals who rated themselves higher in conscientiousness were significantly less likely to notice the unexpected event, and while the relationship was no longer significant after controlling for individual differences in processing speed, the same trend between conscientiousness and IB persisted. This relationship between conscientiousness and IB is in contrast to our own work that used a similar sustained IB task (Wright, Boot, & Morgan, 2013) and other work that used a static IB task (Kreitz, Schuerch, Gibbons, & Memmert, 2015). Kreitz and colleagues (2015) suggest that demands of the primary task may account for differences in findings across studies.…”
Section: Discussioncontrasting
confidence: 99%
“…This is consistent with previously shown strong associations between neuroticism and positive schizotypy [46][47][48][49][50][51], suggestive of aetiological underpinnings [52][53][54][55] with shared genetic etiology [56] and not solely a 'secondary effect' of schizophrenia-spectrum psychopathology. High openness to experience has also been repeatedly associated with positive schizotypy [51,57,58] and its influence extends to the domain of perception [59]. It is interesting that, consistent with the latter, we confirmed this relationship for the ''unusual experiences'' and ''magical thinking'' schizotypy dimensions.…”
Section: Malessupporting
confidence: 85%
“…Researchers expected to find some predictors of IB, but most of them have not found positive results. Kreitz et al (2015b) investigated the relevance of IB and personality traits. They found that openness was a predictor of IB.…”
Section: Discussionmentioning
confidence: 99%